FILM LEGENDA ROGOSELO (Penatas Angin dan Baron Skeber) SEBAGAI MEDIA PENGENALAN WISATA DAN SEJARAH DI KABUPATEN PEKALONGAN - Muhammad Haryanto; Ribut Achwandi; Inayatul Ulya; Amalia Fitri (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This research is aimed to give one of the alternates to promote and develop the tourism, folklore, history and culture in Pekalongan sub-district through a promotion media, film. Besides, it’s hoped that the study of this research will give benefits and can be used as a consideration for the policy makers and the artists of Pekalongan sub-district to find out the solution for the development of   tourism, folklore, history and culture in Pekalongan sub-district. Keywords: folklore, film, tourism